Roteamento de mídia contínua em topologias reais da internet - Eric Rodrigues Guimaraes (2006)
The spreading of high speed network connections has been driving more and more users into using streaming media applications, and therefore motivating the development and deployment of many such applications, either in commercial or institutional scenarios. Streaming media is a real time application, and for that reason it requires that the underlying computational infrastructure provide quality of service (QoS) warranties. Several approaches have been taken in improving QoS for streaming media over best-effort networks like the Internet. As examples of such approaches, there are replication or caching techniques, multicast delivery, and optimized routing. This dissertation focuses on this last approach, dealing with mechanisms which exploit path diversity and multicast routing. Characterizing Internet's path diversity reinforces the first group of works. However, so far the attempts of such characterization only cover some north-american and european ISP. Besides, protocols optimized for multicast routing had only been evaluated in synthetic topologies and a few real topologies. Given previous works' limitations, this dissertation analyzes more deeply the potential gains of using such alternative routing techniques on current Internet topologies.In order to accomplish that, we extend a router-level topology mapping technique and use it to collect real Internet topologies, spread all over the world. We characterize these topologies' path diversity, in order to give support to works which are based on the premise of the existence of such diversity. Our study reveals a high path diversity in wider-area (continental) topologies, and a low diversity in more restricted topologies, such as small countries. We then make an extensive analysis of heuristic protocols which assemble multicast routing trees, proposed by Almeida. Such analysis includes using several topologies in various dispersion levels and varying several parameters, such as the number of client sites and their request rates. Our results show that these heuristics create better multicast routing trees, when compared to the default unicast protocol and similar protocols for multicast, using up to 35% less network bandwidth. Even better savings, of around 70%, where observed in scenarios where most of the sites act both as replicas and clients at the same time.